THE MODERN PARADOX OF FIBERGLASS BOATS: HEALTH AND SAFETY RISK AWARENESS AND ADAPTATION OF FISHERMEN IN EAST LOMBOK, WEST NUSA TENGGARA - Murdi, Lalu; Artaria, Myrtati Dyah; Sutinah, Sutinah (Sosiohumaniora, 2025)
Research on the impact of fiberglass boats has so far focused more on the impact of fiberglass on workers or boat builders. This study aims to provide an analysis of the risks involved in the manufacturing process for the community; the level of comfort and safety when using fiberglass boats; and innovations made to minimise risks and improve comfort and safety. The research approach used is qualitative with an ethnographic method. Data sources include interviews with craftsmen and fishermen in seven villages/areas, observations, documents, and documentation. Data analysis techniques consist of domain analysis, taxonomic analysis, component analysis, and cultural theme analysis. Data validity is strengthened using triangulation. The research findings indicate that: 1) dust from fiberglass boats during sanding in open areas/along the coast poses a risk of causing itching and shortness of breath among the local community, a problem that persists to this day; 2) fiberglass boats are uncomfortable to use, and according to some community members, the vibrations caused by large waves can have adverse effects on heart health; 3) the use of fiberglass boats is considered more risky in terms of safety in the event of an accident; 4) considering the risks, comfort levels, and safety factors, some fishermen have already implemented various innovations.